Fenomena Stigmata dalam Sejarah Kekristenan: Dari Santo Fransiskus Assisi hingga Zaman Modern - Jonathan Octavianus; Hasanema Wau; Donalia Reynaldo (Anugerah : Jurnal Pendidikan Kristiani dan Kateketik Katolik, 2025)
The phenomena of stigmata and divine apparitions represent profound religious experiences that demonstrate the dynamic relationship between faith, body, and consciousness. Through a phenomenological-theological approach and literature review, this study examines how these extraordinary events reflect the spiritual and psychological dimensions of faith. The results demonstrate that stigmata and apparitions are not simply supernatural phenomena, but existential encounters that express human participation in the suffering and presence of Christ. Phenomenological reflection affirms that faith is lived through bodily awareness, not merely understood conceptually. This study emphasizes the importance of discernment and theological interpretation of the church so that extreme religious experiences deepen authentic spirituality, rather than giving rise to superstition. Understanding stigmata and apparitions as transcendental experiences that transcend worldly limitations requires an openness to assess these phenomena in light of the doctrines of Christian faith. Furthermore, this study explores how these experiences contribute to the development of personal and church community spirituality and open up space for deeper reflection on the human relationship with God. Ultimately, this study bridges phenomenology and theology, demonstrating that divine experiences enrich the Christian understanding of the incarnation, suffering, and grace of God present in human existence.